Efficacy of teicoplanin in bloodstream infections caused by Enterococcus faecium: posthoc analysis of a nationwide surveillance. (September 2022) - Ha, Soyoung; Huh, Kyungmin; Chung, Doo Ryeon; Ko, Jae-Hoon; Cho, Sun Young; Huh, Hee Jae; Lee, Nam Yong; Kang, Cheol-In; Peck, Kyong Ran; Song, Jae-Hoon; ,
Highlights : There are limited data on teicoplanin as a treatment for Enterococcus faecium bacteremia. Teicoplanin and vancomycin were compared in a multicenter surveillance. There was no significant difference in 30-day in-hospital mortality. Our findings suggest teicoplanin as a useful alternative to vancomycin. Abstract: Objectives: Vancomycin and teicoplanin are glycopeptides with activity against Enterococcus faecium . However, studies on the clinical efficacy of teicoplanin are limited. This study aimed to compare the therapeutic efficacy of teicoplanin and vancomycin in E. faecium bacteremia. Methods: We identified patients with bloodstream infections prospectively from July 2015 to December 2016 in 14 hospitals as part of a multicenter nationwide surveillance. Patients with E. faecium monomicrobial bacteremia were selected. Teicoplanin and vancomycin groups included patients treated with either agent for ≥48 hours. The primary outcome was 30-day all-cause in-hospital mortality. The Cox proportional hazards model with inverse probability weighting was used to account for the imbalance in baseline characteristics between the two groups. Results: Among 97 patients with E. faecium bacteremia, 33 (34%) were treated with teicoplanin and 64 (66%) with vancomycin. There were no significant differences in 30-day in-hospital mortality (18.2% vs 26.6%, P = 0.358) and 7-day mortality (6.1% vs 15.6%, P = 0.212). Furthermore, multivariable analysis confirmed that the use of teicoplanin was not significantly associated with mortality (adjusted odds ratio, 0.72; 95% confidence interval, 0.28-1.86; P = 0.494). Conclusion: We found no significant differences in the clinical outcomes. These findings suggest teicoplanin as a useful alternative to vancomycin.